Education using Audio Visual media and Sign Language to Increase Children with Disabilities' Knowledge of Fire Disaster Preparedness - Hidayati, Nur; Cahyani, Meilinda Nur; Kusbiantoro, Dadang; Othman, Hamidah (Universitas Negeri Gorontalo, 2025)
Children with disabilities are a vulnerable group during disasters due to the limitations they experience. Disaster risk reduction can be achieved through education, which can be delivered using audio visual media and sign language. The aim of this study is to analyze the impact of audio visual and sign language education on the knowledge of children with disabilities regarding fire disaster preparedness. The research was conducted using a pre-experimental approach with a one-group pre-posttest design involving 25 students with disabilities (visual impairments, hearing impairments, and mild intellectual disabilities) from Junior and Senior High School for special needs in Banjarmendalan, Lamongan Regency, in May 2024. The intervention consisted of audiovisual and sign language education on fire disaster preparedness. The measurement tool used was a questionnaire assessing knowledge, and the data were analyzed using the Wilcoxon test (Î±â‰¤0.05). The results indicated that 56% of students with disabilities had a moderate level of knowledge before the educational intervention, and increased to 68% after the intervention. There was a significant effect of audiovisual and sign language education on the knowledge of students with disabilities regarding fire disaster preparedness (p=0.000). Audio visual and sign language education proved effective in enhancing the knowledge of students with disabilities. However, the effect of the education varied among respondents due to differences in the types of disabilities. Future research is recommended to select specific methods tailored to particular types of disabilities, such as using Braille books for individuals with visual impairments.